Irradiation effects on chemical and functional qualities of ready-to-eat Saengshik, a cereal health food. (June 2020) - Kim, Gui-Ran; Ramakrishnan, Sudha Rani; Ameer, Kashif; Chung, Namhyeok; Kim, Yu-Ri; Kwon, Joong-Ho
Abstract: Saengshik is an uncooked Korean meal comprising of more than thirty different ingredients of plant and animal origins. In Korea, to reduce the microbial loads in the product, electron-beam (EB) or gamma-ray (GR) irradiation at 5 kGy is permitted for its major cereal ingredients. But decontamination effects are not often satisfied. Considering the over-doses in commercial treatment, this study intended to investigate EB and GR irradiations up to 10 kGy on the physicochemical and functional qualities of prepackaged Saengshik . The reducing sugar and amino nitrogen were not significantly affected, whereas total chlorophylls, carotenoids, phenolics, and antioxidant activities were more sensitive to both types of irradiation. Total carotenoids and chlorophylls were reduced at high irradiation doses. In contrast, irradiation increased the free radical scavenging abilities that may be due to increase in total phenolic content (139.63–169.02 mg/100 g, EB; 139.63–168.56 mg/100 g, GR). Although there was slight decrease in the chlorophyll and carotenoid constituents of Saengshik, irradiation up to 10 kGy improved its antioxidant activity without affecting the reducing sugar and amino nitrogen. Dose escalation up to 10 kGy for the cereal product revealed stable reducing sugar and amino nitrogen contents with slight changes below 0.31% in total chlorophylls, carotenoids, phenolics, and antioxidant properties. Highlights: Saengshik is an uncooked product of cereals that needs non-thermal decontamination. E-beam and γ-ray radiation up to 10 kGy increased the total phenolics in Saengshik. Total carotenoids and chlorophylls had an inverse correlation with absorbed dose. Irradiation <10 kGy preserved antioxidant capacity in Saengshik products.